2021
DOI: 10.3390/cancers13215583
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Models of Hepatocellular Carcinoma: Current Strategies for Translational Modeling

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer worldwide and the third leading cause of cancer-related death globally. HCC is a complex multistep disease and usually emerges in the setting of chronic liver diseases. The molecular pathogenesis of HCC varies according to the etiology, mainly caused by chronic hepatitis B and C virus infections, chronic alcohol consumption, aflatoxin-contaminated food, and non-alcoholic fatty liver disease associated with metabolic syndrome or diabetes mellitus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 386 publications
(507 reference statements)
0
13
0
Order By: Relevance
“…The DEN model lacks some vital features in human liver cancer development, such as chronic liver inflammation and liver fibrosis. Thus, additional animal models, especially models with chronic liver inflammation and liver fibrosis, may be needed to further explore the miR-181/CBX7 axis in hepatocarcinogenesis [ 65 67 ]. Second, the miR-181/CBX7 axis might play a role in some human HCCs only, as only one-third of human HCCs show high miR-181 and low CBX7 expressions [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DEN model lacks some vital features in human liver cancer development, such as chronic liver inflammation and liver fibrosis. Thus, additional animal models, especially models with chronic liver inflammation and liver fibrosis, may be needed to further explore the miR-181/CBX7 axis in hepatocarcinogenesis [ 65 67 ]. Second, the miR-181/CBX7 axis might play a role in some human HCCs only, as only one-third of human HCCs show high miR-181 and low CBX7 expressions [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, ANXA3 has been found to not only maintain genomic integrity and facilitate cell proliferation and differentiation but also contributes to tumor initiation and growth. We synthesized the relevant literature and found that that ANXA3 expression was dysregulated in a large number of tumor populations, such as bladder urothelial carcinoma ( 23 ), BRCA ( 17 ), CHOL ( 16 ), COAD ( 24 ), esophageal carcinoma ( 25 ), head and neck squamous cell carcinoma ( 26 ), kidney chromophobe ( 27 ), kidney renal papillary cell carcinoma ( 28 ), hepatocellular carcinoma ( 29 ), LUAD ( 30 ), LUSC ( 31 ), pancreatic adenocarcinoma ( 32 ), PRAD ( 33 ), READ ( 34 ), stomach adenocarcinoma ( 25 ), thyroid carcinoma ( 35 ), and uterine corpus endometrial carcinoma ( 13 ). In this study, an increased ANXA3 expression was associated with a favorable prognosis, suggesting that ANXA3 might play a pivotal role in decreasing cancer risk in patients with OV.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is in line with partially significant differences between the model systems. In some areas of toxicology, one animal species is 60% predictive of another one (Smirnova et al 2018 ), and even strains of mice may show sensitivity differences to carcinogens by > 100-fold (Diwan et al 1986 ; Romualdo et al 2021 ). Understanding the underlying G × E effects is important for the selection of models with the best translational value in toxicology or in disease biology.…”
Section: Model Refinement By G × Ementioning
confidence: 99%